Vaccine hesitancy in patients with COVID-19 who have back pain - Askeri Türken; Haşim Çapar (Osong Public Health and Research Perspectives, 2023)
Objectives Musculoskeletal pain is among the most common symptoms in patients diagnosed with coronavirus disease 2019 (COVID-19), and it has placed a significant burden on health worldwide during the pandemic. This study explored vaccine hesitancy and associated factors in patients with positive COVID-19 polymerase chain reaction test results who were hospitalized and had back pain. Methods A cross-sectional study was conducted among 170 hospitalized COVID-19 patients over 18 years of age. Data were analyzed using descriptive statistics with IBM SPSS ver. 25.0. Results COVID-19 patients who were married considered COVID-19 vaccinations riskier than unmarried COVID-19 patients. Patients who had not been vaccinated expressed higher levels of distrust towards COVID-19 vaccines than patients who had been vaccinated. Participants had relatively little hesitation toward the Sinovac vaccine. High vaccine confidence was found in all participants regardless of vaccination status. Those who had not received the COVID-19 vaccine reported higher risk perceptions than those who had received at least 1 dose of any COVID-19 vaccine. Conclusion Measurements of the hesitancy of vaccinated and non-vaccinated patients or members of society towards vaccines can be an important parameter for health authorities to find solutions.